Slip flow of Casson–Maxwell nanofluid confined through stretchable disks - Gowda, R. J. Punith; Rauf, A.; Naveen Kumar, R.; Prasannakumara, B. C.; Shehzad, S. A. (Indian journal of physics, 2022)
This study reports an incompressible electrically conducting Casson–Maxwell fluid flow confined across two uniformly stretchable disks. Buongiorno nanofluid model is implemented in the fluid flow. Cattaneo–Christov theory of double-diffusion is characterized through the heat and mass equations. Velocity, thermal and concentration slip conditions are executed at the lower stretchable disk. The flow model is dimensionalized through the similarity functions and then numerical solution is attained by RKF-45 scheme combined with shooting technique. The results of physical parameters are discussed by plotting the effects of such parameters on velocity, thermal and concentration fields. The results revealed that the Maxwell liquid is highly effected by Lorentz force than the Casson liquid. Thermal gradient of Maxwell liquid is highly influenced by stretching ratio parameter when compared to Casson fluid. Increase in Casson parameter and Deborah number declines the velocity gradient. Rise in the values of Brownian motion parameter declines the concentration gradient. Finally, the upsurge in thermal relaxation time parameter enhances the thermal gradient quickly in absence of thermal slip parameter.